Evidence from an electronic document in administrative proceedings (Discourse of Law and Administration, 2025)
he article addresses issues related to the functionality of an electronic document, as provided for in Article 3(2) in connection with Article 3(1) of the Act on Informatisation of the Activities of Entities Performing Public Tasks, as evidence in general administrative proceedings, considered, among other things, in the context of changes to the Code of Administrative Procedure resulting from the Act on Electronic Delivery of Documents. In connection with the resignation of operating in the nomenclature of the Code with terms such as: ‘electronic document’, ‘form of electronic document’ within the meaning of the Act on Informatisation of the Activities of Entities Performing Public Tasks, the assessment of the essence and function of the electronic document defined in Article 3(2) in connection with Article 3(1) of the Act on Informatisation of the Activities  of Entities in administrative evidence proceedings becomes an even more complex legal issue than before. Consequently, the subject of consideration was the important issues related to the determination of the meaning scope of the notion of ‘electronic document’ as provided for in Article 3(2) in conjunction with Article 3(1) of the Act on Informatisation of the Activities of Entities, in legal terms in the context of the regulations of the Code of Administrative Procedure; the issue of the legal qualification of documents and other legally relevant data that can be materialised in these proceedings in an electronic form – an electronic document – and their formal and legal typification on the basis of the regulations of the Code of Administrative Procedure, taking into account the contractual criteria for the classification of means of evidence adopted in the doctrine of administrative process.
Keywords: administrative proceedings; electronic document; letter recorded in electronic form; evidence from an electronic document; electronic material